Potential effect of pH on the leaching of heavy metals from sediments of the Carpathian dam reservoirs - Szarek-Gwiazda, Ewa (Geology, Geophysics and Environment, 2015)
Eutrophication processes occurring in the Carpathian dam reservoirs (southern Poland) has resulted in a drastic increase of incidences of decrease of pH and oxygen content in near-bottom water, which may affect metal remobilization from the sediment. The study is aimed to determine the buffer capacity and effects of lowering of pH on remobilization of heavy metals (Cd, Pb, Cu, Zn, Mn and Fe) from sediments of the Dobczycki Reservoir (DR), the Czorsztyński Reservoir (CR), and the Rożnowski Reservoir (RR), the right side tributary of the Vistula River. Buffering capacity and the leaching of heavy metals from sediments accompanied with an increase in acidity were analyzed in 0-0.24M solutions of HNO3. Studied sediments had a good buffer capacity. Buffer capacity of sediments at studied sites of the DR and CR were different due to varied sediment composition. The reservoir sediments had a varied ability to release the metals with increasing acidity. At pH 5 and pH 3, a considerable leaching of Mn (up to 60% and 85% of the total amount, respectively), Cd (up to 35% and 56% respectively), Pb (up to 25% and 39), the lower leaching of Cu (up to 18% and 30%) and Zn (up to 14% and 20%) and slight one of Fe (below 5%) were found. The lowering pH of the water- sediment system caused by eutrophication processes may affect the mobilization of certain heavy metals (mainly Mn, Cd and Pb) from the sediment into the water column of studied Carpathian reservoirs.